Preventive effect of dietary astaxanthin on UVA-induced skin photoaging in hairless mice - Komatsu, Toshiyuki; Sasaki, Suguru; Manabe, Yuki; Hirata, Takashi; Sugawara, Tatsuya (PLOS ONE, 2017)
Astaxanthin, a carotenoid found mainly in seafood, has potential clinical applications due to its antioxidant activity. In this study, we evaluated the effect of dietary astaxanthin derived from Haematococcus pluvialis on skin photoaging in UVA-irradiated hairless mice by assessing various parameters of photoaging. After chronic ultraviolet A (UVA) exposure, a significant increase in transepidermal water loss (TEWL) and wrinkle formation in the dorsal skin caused by UVA was observed, and dietary astaxanthin significantly suppressed these photoaging features. We found that the mRNA expression of lympho-epithelial Kazal-type-related inhibitor, steroid sulfatase, and aquaporin 3 in the epidermis was significantly increased by UVA irradiation for 70 days, and dietary astaxanthin significantly suppressed these increases in mRNA expression to be comparable to control levels. In the dermis, the mRNA expression of matrix metalloprotease 13 was increased by UVA irradiation and significantly suppressed by dietary astaxanthin. In addition, HPLC-PDA analysis confirmed that dietary astaxanthin reached not only the dermis but also the epidermis. Our results indicate that dietary astaxanthin accumulates in the skin and appears to prevent the effects of UVA irradiation on filaggrin metabolism and desquamation in the epidermis and the extracellular matrix in the dermis.